No Save Place for Girls: Study on Sexual Harassments and Violence Against Girls in Indonesia - Suyanto, Bagong (Advances in Social Sciences Research Journal, 2015)
This study investigates the incidents of sexual harassments and violence against girls in Indonesia. Based on this research, girls are more likely to become victims of harassment and sexual violence due to their socially weak position and the domination of patriarchal culture. Therefore, they are easily intimidated, violated, and fooled by the perpetrators. Basically this paper is resulted from a qualitative study by analyzing news data from two mass medias (Jawa Pos and Surya) during January 2012- August 2013, and previous studies on sexual harassment against children. In order to provide a comprehensive analysis, this paper uses the concept of gender-based power relations. Using the news media coverage and field study in this area, this paper examines types of harassments and violences against girls in Indonesia and analyse the causes of sexual violences against teenage girls in contemporary Indonesia. I also argue that the patriarchal values and gendered bias system appear to be the main hurdle for women, especially teenage girls, in Indonesia to resist and being saved from the violence actions sexually and predominantly done and accused by the men, especially the girls’ father. When wise words saying "the kindest and safest man for girl is her father," this words seem do not occur for unfortunate girls studied in this paper."